Control problems for the telegraph and wave equation networks. Issue 1 (March 2021) - Alam, M; Avdonin, S; Avdonina, N
Abstract: In this paper we consider control problems for the telegraph equation networks or, in other words, telegraph equations on metric graphs. If a network is homogeneous, i.e. its parameters are the same for all edges of the graph (and in some other cases), the problem can be reduced a control problem for the wave equation. For graphs without cycles, we obtain necessary and sufficient conditions of exact boundary controllability of the telegraph equation network and find the sharp time of controllability.